2019
DOI: 10.1088/1361-6382/ab06e2
|View full text |Cite
|
Sign up to set email alerts
|

Gravitational collapse of a massless scalar field in a periodic box

Abstract: Gravitational collapse of a massless scalar field with the periodic boundary condition in a cubic box is reported. This system can be regarded as a lattice universe model. We construct the initial data for a Gaussian-like profile of the scalar field taking the integrability condition associated with the periodic boundary condition into account. For a large initial amplitude, a black hole is formed after a certain period of time. While the scalar field spreads out in the whole region for a small initial amplitu… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
4
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 46 publications
1
4
0
Order By: Relevance
“…It is found from this figure that CMC slices do not pass through the black hole region but the white hole region. A similar slice is observed in an analysis of massless scalar field collapse in an expanding background [29]. In order to understand the spacetime structure of a numerical solution, one useful way is to find marginally trapped surfaces associate with the outgoing or ingoing null vector fields.…”
Section: B Cmc Slices In the Kruskal Diagramsupporting
confidence: 52%
See 2 more Smart Citations
“…It is found from this figure that CMC slices do not pass through the black hole region but the white hole region. A similar slice is observed in an analysis of massless scalar field collapse in an expanding background [29]. In order to understand the spacetime structure of a numerical solution, one useful way is to find marginally trapped surfaces associate with the outgoing or ingoing null vector fields.…”
Section: B Cmc Slices In the Kruskal Diagramsupporting
confidence: 52%
“…Actually, in Ref. [29], one of the present authors and his collaborators have revealed the spacetime structure by virtue of the results given in this paper. This is an example showing that the knowledge about the sequence of CMC slices obtained in this paper helps in understanding the spacetime structure of the numerical spacetime solution.…”
Section: B Cmc Slices In the Kruskal Diagrammentioning
confidence: 55%
See 1 more Smart Citation
“…We choose an initially expanding spacetime with K = −3H 0 , so that the periodic integrability condition is satisfied 4 [122][123][124]. The eventual Hamiltonian constraint only depends on the radial coordinate r due to the spherical symmetry of the setup, and we solve for the conformal factor ψ numerically…”
Section: Jcap03(2022)029mentioning
confidence: 99%
“…Note that the condition from the linearisation will be different if ρ = ρ(ψ), as it is the case for the gradient energy density of a scalar field, with ρ ∼ ψ −4 (∂iϕ) 2 and one can choose a constant K that satisfies the integratibility condition[22][23][24][26][27][28].…”
mentioning
confidence: 99%